2022
DOI: 10.3892/or.2022.8315
|View full text |Cite
|
Sign up to set email alerts
|

Blue light irradiation inhibits the growth of colon cancer and activation of cancer‑associated fibroblasts

Abstract: Irradiation with a specific wavelength of light using light-emitting diodes (LEDs) has various effects on cells and organisms. Recently, the antitumor effects of visible blue light on tumor cells were reported; however, the mechanism and effects on the tumor microenvironment remain unclear. Human colon cancer cells (HCT-116) were injected into the rectal wall of nude mice. Tumors were irradiated with a 465-nm LED light at 30 mW/cm 2 for 30 min. Tumor volumes and the expression levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…It is particularly interesting in the context of literature reports indicating the use of blue light in cancer therapy. 36…”
Section: Discussionmentioning
confidence: 99%
“…It is particularly interesting in the context of literature reports indicating the use of blue light in cancer therapy. 36…”
Section: Discussionmentioning
confidence: 99%
“…All previous studies that we have been able to find used high‐power BL irradiation for 30 min to 24 h to investigate the effects on cancer cells. 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 The concept of our study, with an eye toward initial clinical application, was to implant small wireless LEDs in the body and continuously irradiate the tumor. Therefore, it was necessary to develop an experimental model in which BL was irradiated at the lowest possible power for a long period of time, for example, up to 72 h. Recent studies have reported remarkable progress in the development of small wireless LEDs, and data from mouse animal experiments using small wireless LEDs in the fields of photodynamic therapy 41 and photoimmunotherapy 42 suggest the potential for these devices in BL therapy applications.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that continuous irradiation of SS cells with a very low‐power BL source showed marked antitumor effects. All previous studies that we have been able to find used high‐power BL irradiation for 30 min to 24 h to investigate the effects on cancer cells 9–22 . The concept of our study, with an eye toward initial clinical application, was to implant small wireless LEDs in the body and continuously irradiate the tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 Our previous works also show that blue light irradiation can regulate the tumor immune microenvironment via NF-κB signaling pathway and promote the secretion of immunoactive cytokines in skin. 11,15,16 As the main source of ROS, mitochondria have been reported to be important organelle in the "photobiomodulation" process induced by blue light. 17,18 The respiratory complex of the mitochondrial electron transport chain contains iron porphyrin proteins, which are capable of specific absorption for shortwavelength light.…”
mentioning
confidence: 99%